Greenland, view of Kjerulf Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 1, 1931. Kjerulfs [Kjerulf] Fjord. Inner end looking north. This is the north end of L.A.B.'s Main Valley; arrow marking place where we left our motorboat on the west shore (left in photo) near the line of 55 stranded bergs which stretched across the fjord. In the foreground floor of the Main Valley.